Reconstructing Regulations on Compensation Payments in Corruption Cases Based on the Principles of Justice in Pancasila - Anis Mashdurohatun; Salomo Saing; Surya Budi Darma; Sobrani Binzar; Denys Denyshchuk; B.A.S Faomasi Jaya Laia (Nusantara: Journal of Law Studies, 2026)
This study examines the reconstruction of regulations governing compensation payments in corruption cases through the principles of justice embodied in Pancasila. The existing implementation of substitute money sanctions under Article 18(1)(b) of Indonesia’s Corruption Eradication Law has not yet achieved substantive justice, particularly in recovering state financial losses caused by corruption offenses. The study aims to identify the normative and institutional weaknesses within the current legal framework and formulate a justice-oriented reconstruction model grounded in Pancasila values. Using a socio-legal approach developed by Sabian Utsman, this research combines normative legal analysis with empirical examination of institutional practices and living law within Indonesian society. The findings reveal several structural deficiencies, including the absence of explicit asset tracing mechanisms, unclear enforcement timelines, weak coordination among enforcement agencies, and unequal treatment between individual and corporate offenders. These deficiencies allow certain perpetrators to conceal assets, evade financial accountability, and shift the punitive burden toward imprisonment rather than restitution of state losses. The fragmented coordination between the Corruption Eradication Commission, Prosecutor’s Office, Financial Transaction Reports and Analysis Center, and Ministry of Finance further weakens the effectiveness of compensation enforcement. This study proposes a reconstruction of Article 18(1)(b) by integrating comprehensive asset tracing procedures, interinstitutional coordination mechanisms, proportional sanctions, and restorative accountability principles. The reconstruction is philosophically grounded in the principles of divinity, humanity, unity, deliberation, and social justice contained in Pancasila. This research contributes to the development of progressive anti-corruption law by repositioning substitute money sanctions as an instrument of restorative state asset recovery and substantive justice rather than merely a complementary criminal punishment.